Ethnic and confessional factors of comfort of the urban space in the Russian Arctic - Ilya F. Vereschagin; Anton M. Maksimov (Arctic and North, 2019)
The article deals with the influence of the ethnic and religious structure of the population of large cities of the Russian Arctic on the comfort of the urban space. The authors highlight the basic requirements for the urban area by social groups, based on their ethnic and religious affiliation. The main urban objects and spaces naturally and historically created for the needs of ethnic and religious groups are determined. The study used methods of social mapping, observation, analysis of statistical data. On the example of large cities in the regions of the Russian Arctic, the authors show the unsystematic nature of meeting ethnic and religious needs in the creation of comfortable urban space. According to the authors, this is primarily due to the diverse history of urban settlements in the Arctic zone, as well as the functional purpose of settlements, which differ in number and composition of residents. Based on this differentiation, the corresponding types of urban settlements are distinguished. Based on the relatively successful example of the policy of the capital region, the article makes recommendations for improving the proper administration of the urban municipalities of the Russian Arctic. Attention is drawn to the possible features of such a policy, considering the specifics of the Arctic cities and migration processes taking place in the region.